(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Educational systems consist of many elements, including students, teachers, curriculum, administrators, specialists, technology, physical and financial resources. However, teachers are the essential element, since quality of the education mostly depends on the quality and competence of teachers. Most people are familiar with only the computational aspects of mathematics and so are likely to argue for its place in the school curriculum and for traditional methods of instructing children in computation. In contrast, mathematicians see computation as merely a tool in the real stuff of mathematics, which includes problem solving, and characterizing and understanding structure and patterns. The current debate concerning what students should learn in mathematics seems to set proponents of teaching computational skills against the advocates of fostering conceptual understanding and reflects the wide range of beliefs about what aspects of mathematics are important to know.